Interdisciplinary Strategies for Optimizing Prenatal Genetic Screening in Family-Centered Care Systems - Altherwi, Ali Ahmad; Hamoud Awad Al-Harbi; Matar Omishan Alhazmi; Fahad Lafi Aljohani; Yasser Ali Mubrk Alsuhimi; Abdullah Mastour M; Naif Gobishan ALsuhaymi; Ataallah Awadh Alsehaimi; Turke Ali Alajmi; Ahmad Abdulsattar Zaghoun; Marwan Saud Alharbi; Faisal Khalid A Zakri (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Prenatal genetic screening has evolved from basic serum tests into a sophisticated component of modern reproductive care, capable of assessing risk for a wide range of fetal chromosomal and genetic conditions. This expansion, which now includes first and second-trimester serum analytics, nuchal translucency ultrasound, cell-free DNA (cfDNA) testing, and universal carrier screening, necessitates a highly coordinated and informed approach to ensure equitable and effective patient care. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">This article aims to outline interdisciplinary strategies for optimizing prenatal genetic screening within a family-centered care model. It emphasizes the critical role of patient education, shared decision-making, and the careful integration of various screening modalities to support informed reproductive choices. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">The review synthesizes established clinical procedures and guidelines, detailing the technical execution of screening methods, appropriate specimen collection, and the interpretation of complex results. It highlights the importance of pre-test and post-test genetic counseling to navigate the benefits, limitations, and potential outcomes of each testing pathway. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">A patient-centered approach, where all pregnant individuals are offered screening regardless of perceived risk, is fundamental. While cfDNA offers high sensitivity for common aneuploidies, factors like low fetal fraction can lead to indeterminate results. All positive screens require confirmation with diagnostic procedures like amniocentesis. Effective management relies on clear communication among clinicians, genetic counselors, sonographers, and laboratory staff. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Optimizing prenatal genetic screening requires a collaborative, interdisciplinary effort focused on patient safety, education, and ethical counseling. This integrated model empowers families with knowledge, facilitates early diagnosis and planning, and ultimately improves maternal-fetal outcomes.